Perbedaan Massage Woolwich Dan Massage Rolling (Punggung) Terhadap Peningkatan Produksi Asi Pada Ibu Postpartum - badrus, arkha rosyaria (Faculty of Health Sciences , Dr. Soetomo University, 2018)
Abstract : allegedly of postpartum mothers experiencing substandard milkproduction while nursing her baby. Physical and hormonal changes, cause discomfort which causes less current milk production. One of the causes of substandard milk production due to psychological factors, insecurity in the capital to meet the needs of the baby in breastfeeding. BPM research studies in Sri Umi Wahju DJati on postpartum mothers 20. 10 (50%) of people getting massage treatment Woolwich and 10. (50%) of people getting treatment rollingmassage (back). Partum mothers who do not breastfeed their babies, have the possibility ofgetting the baby is not immune either. Therefore, breastfeeding is very important to the growth and development of infants. Purpose study: to determine differences in Woolwich massage and rolling massage (back) to increase milk production in postpartum mothers. Methods: The study was conducted in BPM Sri Umi Wahju Djati followed by a visit homefor 3 weeks with a frequency of 15 minutes of massage. The study used a pre experimental approach to pre - and post without control. The study design is the measurement of milk production with observation sheets and questionnaires. Data were collected in August 2017. The total sample of this research is 20 respondents. Result: The data obtained are not normally distributed, statistical test using chi square test p value: 0,113, since the value of p>0.05 means there is no difference between Woolwich massage and rolling massage (back) toincrease milk production in mothers postpartum.Keywords: Woolwich massage,rolling massage(back), milk production